The Therapeutic Potential of Monocyte/Macrophage Manipulation in the Treatment of Chemotherapy-Induced Painful Neuropathy - Montague, Karli; Malcangio, Marzia (Frontiers in Molecular Neuroscience, 2017)
In cancer treatments a dose-limiting side-effect of chemotherapeutic agents is the development of neuropathic pain, which is poorly managed by clinically available drugs at present. Chemotherapy-induced painful neuropathy (CIPN) is a major cause of premature cessation of treatment and so a greater understanding of the underlying mechanisms and the development of novel, more effective therapies, is greatly needed. In some cases only a weak correlation between chemotherapy-induced pain and neuronal damage is observed both clinically and pre-clinically. As such, a critical role for non-neuronal cells, such as immune cells, and their communication with neurons in CIPN has recently been appreciated. In this mini-review, we will discuss pre-clinical evidence for the role of monocytes/macrophages in the periphery in CIPN, with a focus on that which is associated with the chemotherapeutic agents Vincristine and Paclitaxel. In addition we will discuss the potential mechanisms that regulate monocyte/macrophage-neuron crosstalk in this context. Informed by pre-clinical data, we will also consider the value of monocytes/macrophages as therapeutic targets for the treatment of CIPN clinically. Approaches that manipulate the signalling pathways discussed in this review show both promise and potential pitfalls. Nonetheless, they are emerging as innovative therapeutic targets with CX3CL1/R1-regulation of monocyte/macrophage-neuron communication currently emerging as a promising front-runner.